Fundamental material properties of the 2LiBH4-MgH2 reactive hydride composite for hydrogen storage: (II) Kinetic properties - Jepsen, Julian (2018)
Reaction kinetic behaviour and cycling stability of the 2LiBH4-MgH2 reactive hydride composite (Li-RHC) are experimentally determined and analysed as a basis for the design and development of hydrogen storage tanks. In addition to the determination and discussion about the properties; different measurement methods are applied and compared. The activation energies for both hydrogenation and dehydrogenation are determined by the Kissinger method and via the fitting of solid-state reaction kinetic models to isothermal volumetric measurements. Furthermore, the hydrogen absorption-desorption cycling stability is assessed by titration measurements. Finally, the kinetic behaviour and the reversible hydrogen storage capacity of the Li-RHC are discussed.